PENGARUH PEMULIHAN GIZI BURUK RAWAT JALAN SECARA KOMPREHENSIF TERHADAP KENAIKAN BERAT BADAN, PANJANG BADAN, DAN STATUS GIZI ANAK BATITA (EFECTS OF COMPREHENSIVE OUTPATIENT CARE ON WEIGHT AND HEIGHT INCREAMENT, AND NUTRITIONAL STATUS AMONG SEVERELY MALNO - Arnelia, Arnelia; Irawati, Anies; Lamid, Astuti; Fajarwati, Tetra; Rakhmawati, Rika (Penelitian Gizi dan Makanan (The Journal of Nutrition and Food Research), 2013)
ABSTRACT Background: Outpatient care is a new approach for severely acute malnourished children while the other is inpatient care. To increase and optimalize outpatient care at Nutrition Clinic in Center for R&D in Nutrition and Food (CRDNF) Bogor, the comprehensively treatment was performed including health, nutrition and caring practices. Objectives: To analyse weight and height increament and the nutritional status of under-three years children during outpatient care of severely malnourished children. Methods: An intervention study was implemented to severely malnourished children who participating in a 6 months outpatient care at Nutrition Clinic in CRDNF, Bogor. The comprehensive treatments were: curing the illness, nutrition and health counseling, gradually dietary treatment, caring guidance. The control groups were treated as the regular treatment of the clinic, including curing the illness, nutrition and health counseling and skim milk ration. Results: The average weight increament among comprehensive group significantly higher than those of reguler group, that was 1.39 ± 0.66 kg and 0.80 ± 0.40 after 3 months (p=0.001) and at the end of out patient care was increased 2.02 ± 0.85 kg and 1.39 ± 0.52 consecutively (p=0.008). No different was found on the increament of childs length/height after 6 months out patient care, that was 4.0 ± 2.0 cm dan 4.1 ± 1.3 cm (p=0.806). After 3 months, 58.3% of comprehensive group and 22.7% of reguler group increased their weight by >15%, and to 73.9% and 50% after 4 months intervention. Based on W/H category, 79.2% of the comprehensive groups were severe wasting while in reguler group 59.1% and the rest were wasting at the beginning of the study. After 3 months intervention, 50% of the comprehensive group and 27.3% of the reguler group were normal and by the end increased to 73.9% and 33.3%. Conclusion: The increament of weight and the nutritional status improvement was much better among comprehensive care than that of the regular care. [Penel Gizi Makan 2010, 33(2): 125-137] Keywords: severe acute malnutrition, severe wasting, out-patient, comprehensive